Learning English in Third Grade through Powtoon - G.A.P., Suprianti; N. W. S., Mahayanti; P.A.A.G, Suarjaya (Journal of Education Technology, 2020)
Nowadays, the English teachers in elementary school still use conventional media in teaching English. Based on the phenomena, the researcher developed a media with the aimed to develop Powtoon animation based-video for teaching third-grade students of elementary school. The data of this research were collected through interview, syllabus analysis, students’ questionnaire, and document recording. ADDIE model by Romiszowski was developed as the procedure of this research. The result of this research was PowToon animation based-video can be used to teach English for third-grade students of elementary school. From the students’ questionnaire, it found that the animation video could attract the students’ attention and it also motivated the students during the teaching and learning process. The media was categorized as good media by conducting expert judgment rubric. So, PowToon animation-based video could be used as an alternative media in learning English.